A study on the applicability of the Strengths and Difficulties Questionnaire among low- and higher-educated adolescents - Theunissen, Meinou H. C.; de Wolff, Marianne S.; Eekhout, Iris; van Vulpen, Coryke; Reijneveld, Sijmen A. (Frontiers in Psychology, 2024)
Aim The Strengths and Difficulties Questionnaire self-report (SDQ-SR) is a valid instrument for detection of emotional and behavioral problems. The aim of this study was to compare the psychometric properties of the SDQ-SR for low and higher educated adolescents, and to explore its suitability. Methods We included 426 adolescents. We compared internal consistency for low-educated, i.e., at maximum pre-vocational secondary education, and higher educated adolescents and assessed whether the five-factor structure of the SDQ holds across educational levels. We also interviewed 24 low-educated adolescents, and 17 professionals. Results On most SDQ subscales the low-educated adolescents had more problematic mean scores than the higher educated adolescents. Findings on the invariance factor analyses were inconsistent, with some measures showing a bad fit of the five factor model, and this occurring relatively more for the low-educated adolescents. Professionals and adolescents reported that the SDQ included difficult wordings. Discussion Our findings imply that the scale structure of the SDQ-SR is slightly poorer for low educated adolescents. Given this caveat, psychometric properties of the SDQ-SR are generally sufficient for use, regardless of educational level.